Voluntary cardio-respiratory synchronization. - Patterson, R.B (IEEE Engineering in medicine and biology magazine)
During stereovectorelectrocardiographic (SVEC) measurements, respiration influences the cardiac vector. This cardiac vector is modulated by the change in the heart position due to diaphragm movement, changes in conductivity in thoracic tissues caused by lung inflation, and shifts in the blood volume. For years, the only method to control the respiratory induced variation was for subject or patient to hold his breath, that was until the voluntary cardio-respiratory synchronization (VCRS) technique. The VCRS technique involves instructing a subject to breathe in synchronization with his/her heartbeat by using either a light or sound signal. Triggered by the R wave of the electrocardiogram, the device signals the subject when to inhale and exhale based on a fixed number of heart beats for each phase of the respiratory cycle. With VCRS techniques, respiratory influences of heart rate variability (HRV), which are mostly parasympathetic, can be separated from nonrespiratory effects, in which sympathetic influences may dominate along with very slow changes due to thermo-regulation and other factors. This work shows how VCRS can be used in unique ways to measure HRV and also separate out respiratory influences on other cardiovascular signals.